Stewardship 2.0: Embracing elements of implementation science to enhance everyday antimicrobial Stewardship efforts - Elizabeth Monsees; Ann L. Wirtz; Sarah Krein (Cambridge University Press, 2023)
This article explores the utility of implementation science (IS) as a method to promote the effective uptake of antimicrobial stewardship processes. Elements of IS can be readily incorporated into QI work and used as a platform to extend stewardship reach. As stewards are stretched to do more, IS can be a potential vehicle to ensure that our collective work is impactful, sustainable, and contributes more broadly to clinically relevant improvements.